Renúncia de receita tributária: o caso do estado do Pará - MALCHER, Carolina Sequeira Zurita Gama (Universidade Federal do Pará, 2015)
This paper aim to assess the institute of tax waiver. The practice of offering tax incentives which results in tax waiver is widely spread all of the world to assist the development of strategic economical segments, disadvantaged regions and groups of taxpayers, however, it should not happen indiscriminately, because it can affect the balance of public finances. It is in this statement which lies the doctrine of tax expenditure which equates, for budget purposes only, the losses of revenue from the tax waivers as the government expenses. Nationally, the concern with the amount and control over the tax expenditures lies in the Federal Constitution of 1988, which determines, on the article 165, § 6th that the project of budget law will be followed by regional demonstrative of the effects of tax waiver. The theme of the tax waiver gained popularity with the advent of the Complementary Law nº 101, dated on May 4th, 2000, named as Fiscal Responsibility Law, which establishes regulations of public finances oriented to the responsibility of tax management; adopts the international concept of tax waivers as tax expenditures; and incorporates in the budgets laws the financial effects of tax waivers. Besides the requirements presented in the Fiscal Responsibility Law and the compliance of the disposed on article 165 of the Federal Constitution, the concession of tax exemptions should always concur with the promotion of social welfare, or rather, for the offering or widening of tax incentives which results in tax waiver is necessary the existence of a public interest that justifies the act, and gives legitimate to this waiver. Besides the theoretical approach of the institute in question, this current research aims to verificate, in the concrete case, the use that the State of Pará makes of this institute.